Penyusunan Bibliografi Beranotasi Subjek Hak Asasi Manusia Koleksi Perpustakaan Komnas Ham Kota Padang - Syahputra, Bambang Eka; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractIn this paper discussed, first compilation of annotated bibliography, both obstacles and attempts in the compilation of bibliography annotated book the subject of human rights collection Library Komnas HAM of Padang. The purpose of this paper is to describe the compilation of bibliography of the collection of human rights subjects in the Library of Komnas HAM of Padang City in order to assist the librarian and librarian in finding the needed information easily and quickly. The method used in the writing of this paper is a descriptive method, which describes the findings or research data. The compilation of an annotated bibliography of human rights subjects in the Library of Komnas HAM of Padang was conducted by collecting data directly from the original source, the human rights subject book at Komnas HAM Library of Padang City. Based on the results obtained, the number of books on human rights subjects amounted to 100 books. Based on the compilation of an annotated bibliography of human rights subjects the collection of Komnas HAM Library of Padang City can be concluded several stages in the making of annotated bibliography: first the title of bibliography is based on the consideration of the availability of books collection with the subject of human rights, the collection of collections by the users based on the most popular information , the need for documentation that includes the collection, processing and storage of information; second collection of bibliography by recording bibliographic data of author's name, book title, and other information such as call number; the third selection of library materials is done by separating books subjected to human rights with books that are not subject to human rights; the fourth grouping or classification is done so that books with the same subject will be grouped in close proximity; the five key word-making is done by describing a subject matter so that the reader can understand and simplify the tracing of information that has been collected in a bibliographic list; Sixth Index compilation based on author index, title index and keyword index; the seven typing bibliographic texts; the eight final bibliographic manuscript examination is done by examining spelling errors and misleading punctuation of points or distances between the less appropriate sentences.Keywords: Bibliography, Book Archives, Library.